Production of valuable pyrolytic oils from mixed Municipal Solid Waste (MSW) in Indonesia using non-isothermal and isothermal experimental - Indra Mamad Gandidi; M. Dyan Susila; Nugroho Agung Pambudi (Case Studies in Thermal Engineering, 2017)
Municipal solid waste (MSW), disposed of at open dumping sites, poses health risks, contaminates surface water, and releases greenhouse gasses such as methane. However, pyrolysis offers the opportunity to convert MSW into Bio-Oil (BO) for clean energy resource. In this paper, an MSW sample consisting of plastic, paper and cardboard, rubber and textiles, and vegetable waste is pyrolysed on a laboratory scale in a fixed-bed vacuum reactor. In the non-isothermal process, the sample was fed into the reactor and then heated. In the isothermal process, the reactor is first heated and then the sample is added. The non-isothermal process created greater BO in both quality and quantity. The BO had a larger amount of gasoline species than diesel-48 fuel, with at 33.44%the BO produced by isothermal pyrolysis and 36.42% in non-isothermal pyrolysis. However the product of isothermal pyrolysis had a higher acid content that reduced its heating value.